Construction and validation of an educational booklet for patients in the postoperative period of cardiac surgery: a methodological study - Sônia Regina Barcellos; Alexandre do Rosário Joras; Angelita Paganin Constanzi; Emiliane Nogueira de Souza (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to construct and validate an educational booklet for self-care of patients in the postoperative period of cardiac surgery Methods: methodological study, including bibliographic survey, construction of the booklet and validation with judges and the target audience. For validation with judges, the Health Educational Content Validation Instrument was used, and with the target audience, an instrument was used with questions related to organization, writing style, appearance and motivation. To analyze the judges' answers, the content validation index was used Results: the booklet was prepared with 14 topics. The content validation index among the eight judges was 1 and the concordance index among the ten patients was above 80%. The final version of the material was made available in printed format Conclusion: the educational booklet was developed and validated by judges and the target audience, serving as an educational support tool for self-care of patients in the postoperative period of cardiac surgery.